IgA Production Alter Administration of a Probiotic - Gigola, G. (2007)
Probiotics are live microorganisms that exert health beneficial actions to the host after their oral administration if they are given in suitable amounts. They have a stimulatory effect on humoral immunity by increasing the amount of available local and circulating IgA. However, it is possible that continuos administration might not be the optimal way to administer them. Our objective was to compare two doses of probiotics and study their effect on local immunity in rat intestine. For this purpose we used 27 rats that were divided in three groups: Control group (3 animals), Group A (15 animals ) and group B (9 animals ). Group A was given 1 ml of BIOFLORA (SIDUS Lab) and Group B 0,2 ml. Animals were sacrificed at 3,5,8,10 and 15 weeks of treatment and intestine was resected and processed by freezing technique. Immunofluorescence was performed in order to study the amount of IgA+ cells. Results: BIOFLORA stimulated the production of IgA secretory cells in groupAwith a peak at 3 days whereas in group B it did not exert significant effects with respect to control animals. The amount of IgA+ cells returned to basal values after 8 days of treatment. The results suggest that the increase in IgAsecretory cells is dependent on the dose of probiotic and the period of treatment and that it is possible that a cyclic treatment would be a better way of administering the probiotic